Theoretical studies of pressure induced structural phase transformation and elastic properties in nickel silicide. (2022) - Malviya, Sheetal; Dixit, R.C.; Choudhary, K.K.; Kaurav, Netram
Abstract: In this study, we have explored pressure dependent structural phase transformation and related volume collapse in the vicinity of transition in Nickel Silicide (NiSi) with the help of an effective inter-ionic potential approach. It was observed that by employing an effective interionic interaction approach, which is basically based on phenomenological models of lattice dynamics, includes the long-range Coulomb, van der Waals (vdW) interaction, and the short-range repulsive interaction in the framework of the Hafemeister and Flygare approach. Our results indicate that the material parameters evaluated by such an approach provide a successful evaluation of the equation of state for change in volume with respect to the applied pressure. The estimated value of phase transition pressure (Pt) is 25 GPa for NiSi, which is in line with the information that we have in the literature. This transition corresponds to the transformation of a B 1 (NaCl) type structure to a B 2 (CsCl) type structure and is a first-order phase transition. This first order phase transformation showed a volume collapse of about 11.44% at 25 GPa for NiSi. Later on, the relationship between pressure and the variation of second-order elastic constants is examined in greater detail.